How often did the Sava River flood in the past? A sedimentological and chronological investigation of terrace overbank sediments, Šabac (Serbia) - Krsmanović, Petar; Constantin, Daniela; Timar-Gabor, Alida; Avram, Anka; Galić, Zoran; Feurdean, Angelica; Perić, Zoran ; 0000-0003-0116-8895; Marković, Slobodan B. (INTERNATIONAL CONFERENCE Geospatial and Environmental Dynamics – LAMINATION, Novi Sad, Serbia, 2025-11-15 - 2025-11-16, 2025)
In this study, we investigated overbank sediments of the first terrace of Sava river in Šabac, exposed at a residential building construction site. Sediment characteristics such as grain size, magnetic susceptibility, chemical composition, and loss on ignition (LOI) at 550 °C and 950 °C were determined at 5 cm resolution, accompanied by visual inspection to assess color, pedogenic structure, and other pedogenic features. A total of eight samples were dated using optically stimulated luminescence (OSL) at two grain-size fractions (4–11 μm and 63–90 μm). The obtained ages were used to calculate mass accumulation rates (MAR). The profile is 2.25 m thick and composed predominantly of clayey loam. The modern soil developed at the site is an anthropogenically modified cambisol, containing a 75 cm thick terric horizon that differs in sedimentological characteristics from the rest of the profile. It is characterized by a higher sand content and increased LOI at 950 °C. The lowermost horizon of this cambisol extends into the late pleistocene, indicating downward progression of the cambic B horizon. The obtained OSL ages reach up to ~32 ka. High MAR values persist until ~19 ka, after which they decrease and remain low toward the present, suggesting incision of the Sava River and subsequent abandonment of this (now former) floodplain. Two peaks in MAR at ~25 ka and ~32 ka correspond to periods of intensified melting of the Alpine ice sheet, indicating that enhanced meltwater discharge led to increased flooding and more rapid accumulation of overbank sediments. The investigated sequence does not record the melting event that occurred around ~28 ka.